[tex]ay^2 + by + c = a(y -y_1)(y - y_2)[/tex]
[tex]y_{1,2} = \frac{-b \pm \sqrt{b^2-4ac}}{2a}\\\\y_{1,2} = \frac{ -7 \pm \sqrt{ 7 ^2 - 4 \cdot 3 \cdot (-20)} }{ 2 \cdot 3 }\\\\y_{1,2} = \frac{ -7 \pm \sqrt{ 289 } }{ 6 }\\\\\\y_1 = \frac{ -7~+~\sqrt{ 289 } }{ 6 } = \frac{ 5 }{ 3 }\\\\y_2 = \frac{ -7~-~\sqrt{ 289 } }{ 6 } = -4[/tex]
[tex]3y^{2}+7y-20 = 3 \left(y - \left( -4 \right)\right)\left(y - \frac{ 5 }{ 3 } \right)\\\\3y^{2}+7y-20 = 3 \left(y + 4 \right)\left(y - \frac{ 5 }{ 3 }\right)\\\\\\3y^{2}+7y-20 = ( y+4 )( 3y-5 )[/tex]